PERAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA PADA UMKM BISNIS JASA DI BULAK KAPAL BEKASI - Budi Muliawan (PARAMETER, 2020)
This study aims to determine the effect of work motivation on employee productivity and how much influence of work motivation on employee work productivity of SME on Bulak Kapal Bekasi. This research is a quantitative descriptive research type. Data were collected using a questionnaire method, which was then analyzed using simple regression analysis using SMART PLS 3.0 for Windows which includes the t test. The results showed that work motivation has a positive and significant effect on employee work productivity, that is indicated by a positive regression coefficient of 8.86 with a value of t = 14.079> t table = 2.042 and a probability value of 0.000 t test which is smaller than α = 0.05. The magnitude of the influence of work motivation on employee work productivity of SME is indicated by the coefficient of determination of 0.78. This shows that 78% of employee work productivity is influenced by work motivation.